A PDCA based approach to evaluate green supply chain management performance under fuzzy environment. Issue 1 (2nd January 2023) - Ghosh, Sudipta; Mandal, Madhab Chandra; Ray, Amitava
ABSTRACT: This paper proposes a novel plan-do-check-act (PDCA) based group decision making model to evaluate the GSCM performance of manufacturing organizations. This research employs an integrated fuzzy multi-criteria decision-making (MCDM) approach in which the fuzzy-analytical hierarchy process (FAHP) method determines criteria weights and the fuzzy-technique for order preference by similarity to the ideal solution (FTOPSIS) method ranks the organizations. Five qualitative criteria are selected from the extant literature, which encompass both environmental, operational, and economic aspects of sustainability. Data is collected by developing a questionnaire, establishing a decision-makers' committee, and carrying out a survey. To illustrate the industrial application of the proposed model, this study considers a real-world case study in the Indian manufacturing sector, in which three organizations (Organization A, Organization B, and Organization C) are selected from three distinct industrial segments, namely the leather industry, the pharmaceutical industry, and the steel industry, respectively. The result reveals that the environmental impact of harmful substances released from production is the most influential parameter. The result also reveals that Organization C is the benchmark organization and its strategies can guide other organizations for GSCM performance improvement. Moreover, the proposed model is capable of handling vagueness and ambiguity in decisions.